11β-hydroxyandrostenedione: Downstream metabolism by 11βHSD, 17βHSD and SRD5A produces novel substrates in familiar pathways. (15th June 2015) - Swart, Amanda C.; Storbeck, Karl-Heinz
Highlights: Human CYP11B enzymes catalyse the 11β-hydroxylation of A4 and T. 11OHA4 is a major C19 adrenal steroid and is metabolised to active androgens. 11KT is a partial agonist and 11KDHT a full agonist, comparable to DHT at 1 nM. 11OHA4 and downstream 11β-hydroxyl metabolites are novel substrates for 11βHSD2. 11OHA4, 11OHT, 11KA4 and 11KT are novel substrates for SRD5A. Abstract: 11β-Hydroxyandrostenedione (11OHA4), a major C19 steroid produced by the adrenal, was first reported in the 1950s. Initially the subject of numerous studies, interest dwindled due to the apparent lack of physiological function and, by the end of the century, 11OHA4 was no longer considered as an adrenal C19 steroid. Our recent studies, however, showed that 11OHA4 is the precursor to novel active androgens which include 11-ketodihydrotestosterone (11KDHT) which has been implicated in prostate cancer, thereby renewing interest in 11OHA4. In this paper we review the biosynthesis and downstream metabolism of 11OHA4. We discuss the extra-adrenal biosynthesis of 11OHA4 in humans and in other species, highlighting the well-documented role of 11OHA4 in the testes of male fish in which the steroid functions as an active androgen. Finally, we discuss the physiological relevance of 11OHA4 metabolism in castration resistant prostate cancer and outline future prospects.